Fetal outcome of pre-labor rupture of membranes - Shrestha, Sita Ram; Sharma, Paban (Nepal Journal of Obstetrics and Gynaecology, 2009)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Objective: To study the determinants and outcome of prelabour rupture of membrane at term pregnancy in Patan Hospital. Method: A prospective, hospital based case control study done in maternity ward of Patan Hospital over the period of three months (Poush 2059-Phalgun 2059). A total no of 100 pregnant women with prelabor rupture of membrane and 100 pregnant women without prelabor rupture of membrane were included in this study. Results: The incidence of pre labor rupture of membrane in this study was 6.06%. Major risk factors for prelabor rupture of membranes were antecedent coitus, hydramnious, smoking, cephalo-pelvic disproportion, and previous abortion. Normal delivery occurred in 70% in prelabor rupture of membrane group and in 93 % in non-prelabor rupture of membrane group. Forty-nine pregnant women with pre-labour rupture of membrane received antibiotics and twenty-four babies (48.98%) developed neonatal infection in pre-labour rupture of membrane group and only one developed infection in non-prelabour rupture. Four cases of neonatal infection was seen in neonates born from mothers with prelabor rupture of membranes < 24 hours and 20 cases of neonatal infection were seen in those neonates born from mother with pre-labor rupture of membrane >24 hours (p < 0.05). Conclusion: Neonatal morbidity increases with the increase of time interval between the rupture of membrane and delivery and antibiotics given to mother of PROM does not totally protect neonates from infection. Keywords: Pre labor rupture of membrane, major risk factors for pre-labor rupture of membranes, neonatal infection doi:10.3126/njog.v1i2.1489 N. J. Obstet. Gynaecol Vol. 1, No. 2, p. 19 -24 Nov-Dec 2006